The effects of serial casting on lower limb function for children with Cerebral Palsy: a systematic review with meta-analysis - Nikki Milne; Michelle Miao; Emma Beattie (BMC, 2020)
Abstract Background Lower limb serial casting is commonly used therapeutically in paediatric clinical practice with some evidence to support its efficacy. This systematic review aimed to determine the effects of serial casting in isolation or combination with other therapies for the management of lower limb dysfunction in children with Cerebral Palsy (CP). Methods A systematic literature search was conducted in February 2019 across eight databases (PUBMED, EMBASE, CINAHL, PEDro, OTSeeker, Cochrane, Scopus and Proquest) using key terms 'Cerebral Palsy' and 'serial casting' and associated synonyms. A meta-synthesis and meta-analysis were undertaken when sufficient results were available showing the effect of serial casting on functional outcomes including: Ankle range of motion; neurological measures of hypertonicity and spasticity, functional gait measures and; gross motor function. Results Twenty-five articles from 3219 possible citations were included. Serial casting was found to be effective for: Improving ankle dorsiflexion (DF) passive range of motion (PROM) in the immediate to short-term, decreasing hypertonicity measured by Modified Ashworth Scale (MAS) in the short-term and, enhancing functional gait outcomes in the mid-term. Serial casting with or without botulinum toxin type-A (BTX-A) did not significantly affect gross motor capacity measured by Gross Motor Function Measure (GMFM). Serial casting with pharmacological intervention achieved significantly more DF PROM than serial casting alone (MD − 3.19 degrees; 95% CI − 5.76 to − 0.62; P = 0.01; I2 = 0%), however the clinical importance of improving ankle DF PROM by an additional three degrees remains unclear. Conclusions Lower limb serial casting, improves several outcomes relevant to lower limb function supporting its clinical use for improving DF PROM, reducing hypertonicity and improving gait in children with CP. Further research using stronger methodological study designs, is indicated to explore long-term effects of serial casting on functional lower limb outcomes such as gross motor function in children with CP. Clinicians can use this information when developing individualised treatment plans for children who have CP during shared decision-making consultations.